2016
DOI: 10.2147/copd.s107938
|View full text |Cite
|
Sign up to set email alerts
|

Smoking-related interstitial fibrosis combined with pulmonary emphysema: computed tomography-pathologic correlative study using lobectomy specimens

Abstract: PurposeTo evaluate the incidence and pathologic correlation of thin-section computed tomography (TSCT) findings in smoking-related interstitial fibrosis (SRIF) with pulmonary emphysema.Patients and methodsOur study included 172 consecutive patients who underwent TSCT and subsequent lobectomy. TSCT findings including clustered cysts with visible walls (CCVW) and ground-glass attenuation with/without reticulation (GGAR) were evaluated and compared in nonsmokers and smokers and among lung locations. TSCT findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
(36 reference statements)
0
10
1
1
Order By: Relevance
“…Our study assessed ILA/ILD patterns on visual inspection of pre-surgical resection CT chest while others have relied on quantitative high attenuation areas (HAAs) to define ILAs [ 22 , 23 ]. Pathological investigation which utilized tissue resected for lung cancer reported a similarly high prevalence of radiographic interstitial changes [ 13 ]. Applying different methodology, a comparable rate of interstitial fibrosis (60%) was pathologically identified in smokers [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study assessed ILA/ILD patterns on visual inspection of pre-surgical resection CT chest while others have relied on quantitative high attenuation areas (HAAs) to define ILAs [ 22 , 23 ]. Pathological investigation which utilized tissue resected for lung cancer reported a similarly high prevalence of radiographic interstitial changes [ 13 ]. Applying different methodology, a comparable rate of interstitial fibrosis (60%) was pathologically identified in smokers [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although comparison of quantitative methods of ILA evaluation to visual ILA showed potential modification from coexisting emphysema (5% or more) [ 8 ], a significant positive association was demonstrated between paraseptal emphysema and ILAs [ 9 ]. Recent studies have suggested that ILAs can show a higher prevalence (23.1 to 40.7%) and are associated with both a worse clinical course and higher mortality rates in COPD patients [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also identified significantly more smokers with lung emphysema in the indeterminate UIP group. Some scans reclassified as indeterminate for UIP with emphysema lesions may have been retrospectively related to both smoking-related interstitial fibrosis (SRIF) and airspace enlargement with fibrosis (AEF) entities (Figure 4) (24,25), which are associated with a slower clinical course than UIP (26). We have not categorized these entities because their diagnostic criteria are not yet sufficiently validated on CT without pathological confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that nonemphysematous cysts usually present as thin-walled, inhomogeneous-sized cysts, and they are characterized by relatively asymmetric distributions and less involvement of the juxta-subpleural parenchyma (Fig. 9) (37)(38)(39). It is one of the imaging features that are predictive of ILA progression (odds ratio: 2.5; 95% CI: 1.3-5.1) and increased mortality (hazard ratio: 1.4; 95% CI: 1.1-1.8) (16), albeit not as strongly as the other features, including reticular markings and traction bronchiectasis.…”
Section: Fibrotic Ilasmentioning
confidence: 99%